How Epistemology Matters: Five Reflexive Critiques of Public Sociology. (January 2013) - Powell, Christopher
This article analyses Michael Burawoy's vision of public sociology in light of five distinct 'epistemic strategies', each of which generates substantially different expectations regarding the challenges and opportunities facing public sociologists. The five epistemic strategies range along a spectrum from methodological individualism at one end to holism at the other. Between these two poles, considerations of the social relativity of scientific knowledge arise. Constructionist theories highlight the performative dilemma entailed when science reveals itself to be one narrative among others. Hierarchical theories such as Marxism suggest that public sociology is torn by the irreconcilable contradiction between hegemony and counter-hegemony. Heterarchical theories address both of these two problems together. Heterarchy suggests that science's claim to universality may interfere with public sociology's social-transformative aspirations. However, the dynamic complexity of 'public' social struggles generates opportunities to rethink the place of difference in the production of scientific knowledge.